Could Intern Health Care Students Control Their Emotions and Make a Career Plan During the COVID-19 Pandemic? - Güngör Tavsanli, Nurgül; Nehir, Sevgi (Inquiry (00469580), 2023)
The negative effects of the pandemic caused students to make changes in their career plans and their ability to manage their emotional states. Not only health students in our country, but also students in other countries of the world experienced fear, anxiety, and unwillingness to participate in professional practices and the provision of care for patients with COVID-19 during the COVID-19 pandemic. The study was conducted to determine factors influencing intern healthcare students' career adaptability and their ability to manage emotions during the COVID-19 pandemic. The sample of this cross-sectional study consisted of 219 intern healthcare students studying at the Faculty of Health Sciences Undergraduate Program of a University in the fall semester of the 2020 to 2021 academic year. The study data were collected online using the Personal Information Form, Career Adapt-Ability Scale (CAAS), and Courtauld Emotional Control Scale (CECS). The data obtained were analyzed by using the independent samples t -test, Analysis of Variance (ANOVA), correlation tests, and the regression model to distinguish variables significantly. Two models explained more than 50% of the variance of CAAS and CECS regarding COVID-19, and 5.1% of the career planning regarding the period during the COVID-19 pandemic (P <.05). As the students' control over their careers decreased during the COVID-19, their feelings of anxiety and unhappiness increased (P <.05). Of the variables, sex, department, future expectations, the position dreamed of being in after graduation, and attitudes toward patient care with COVID-19 affected their CAAS and CECS scores.